Regularity, treatment adherence and outcome among diabetic patients in primary care: an overview - D., Sridhar; K. A., Narayan (International Journal Of Community Medicine And Public Health, 2019)
Early detection and compliance to prescribed treatment is the cornerstone to avert life threatening complications among those with non-communicable diseases (NCD). Assessing regularity of visits, adherence to medication and its correlates can help in devising effective strategies to improve medication adherence. The objective of the study was to review about regularity, treatment adherence and outcome among diabetic patients in primary care. In this literature review, electronic data sources viz. Pub Med, Proquest, Google Scholar, Research gate with the use of the keywords or Mesh words like “Diabetes,” “Primary Health care” “Treatment adherence” “Regularity of treatment” “process of care indicators” and “outcome indicators” were searched. The searches were limited to studies reported in English and were available as free full text from January 2009 to June 2018. Related articles including descriptive cross-sectional, cohort, randomized controlled trials, qualitative studies and systematic reviews were also extracted and refined further. From our review it’s clearly evident that the level of Diabetic care in terms of regularity and follow-up is suboptimal compared to standards established in developed nations. There is a wide scope for improvement in diabetic care as demonstrated successfully in many nations using regular clinical audit, which needs future introspection.